Respuesta :
For the known image point, subtract the coordinates of the corresponding original point. To find the other image points, add that difference to each of the corresponding original points.
Given A and A', compute D = A' - A. The you have
B' = B + D
C' = C + D
_____
Perform the arithmetic on corresponding coordinates. (dx, dy) = (ax' - ax, ay' - ay)
Given A and A', compute D = A' - A. The you have
B' = B + D
C' = C + D
_____
Perform the arithmetic on corresponding coordinates. (dx, dy) = (ax' - ax, ay' - ay)
Translation involves moving a shape away from its original position.
To translate the entire triangle, you need to
- Get the translation rule
- Apply the translation rule
From the question, we understand that:
- The coordinates of the triangle are known
- The coordinates of one of the vertices of the image is known
Assume that, the coordinates of the triangle is as follows
[tex]\mathbf{A = (4,6)}\\\mathbf{B = (5,4)}\\\mathbf{C = (3,0)}[/tex]
Assume one of the vertices of the image is:
[tex]\mathbf{A' = (2,1)}[/tex]
The first thing to do is to calculate the translation rule using the vertex of the image and the corresponding vertex of the pre-image
This is represented as:
[tex]\mathbf{(x,y) = A' - A}[/tex]
[tex]\mathbf{(x,y) = (2,1) - (4,6)}[/tex]
[tex]\mathbf{(x,y) = (2 - 4,1 -6)}[/tex]
[tex]\mathbf{(x,y) = (- 2,-5)}[/tex]
So, the translation rule is:
[tex]\mathbf{(x,y) \to (x- 2,y-5)}[/tex]
Apply the translation rule on other points
[tex]\mathbf{B' = (5-2,4-5)}[/tex]
[tex]\mathbf{B' = (3,-1)}[/tex]
[tex]\mathbf{C' = (3-2,0-5)}[/tex]
[tex]\mathbf{C' = (1,-5)}[/tex]
So, the step to translate the entire triangle is:
- Calculate the translation rule
- Apply the translation rule on other points
Learn more about translations at:
https://brainly.com/question/14090589